Processing retail beef cuts from boxed beef - Leafgreen, M.O.; McCoy, J.H. (Kansas State University. Agricultural Experiment Station, 2011)
This analysis measured efficiencies of a centralized retail meat fabrication facility receiving all beef as boxed or as carcasses. Moving vacuum-packaged, boxed-beef subprimals through a central meat processing facility was more efficient than a corresponding operation with beef carcasses. Boxed beef saved approximately 6.0 cents per pound on wholesale cuts.
Keywords: Beef; Retail cuts; Boxed beef